Use of Mixed Methods in Social Sciences Research - Subedi, Madhusudan (Nepalese Journal of Development and Rural Studies, 2023)
The landscape of social sciences is inherently complex and multifaceted, demanding a comprehensive and nuanced approach to research methodologies. This paper highlights the significance of mixed methods research in addressing the intricate and dynamic nature of social phenomena. Mixed methods not only enhance the validity and reliability of research findings but also allow for a holistic understanding of social phenomena and empower researchers to explore the comprehensiveness and diversity of human experiences, behaviors, and interactions that the traditional single-method approach often falls short of. Furthermore, mixed methods facilitates the triangulation of data, enabling researchers to corroborate and validate results through diverse lenses, thereby fortifying the robustness of their conclusions. Mixed methods contribute to the development of more effective and informed social and public policy interventions. Adopting mixed methods in social science research is not merely a choice but a necessity for unlocking the full potential of inquiry and advancing our collective understanding of the complex social world.